2020
DOI: 10.1088/1402-4896/ab8580
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation into the densification of ferrous powder in high velocity compaction

Abstract: The densification of ferrous powder in high velocity compaction (HVC) is numerically captured by using discrete element method. Macro property (porosity), micro properties (coordination number (CN), radial distribution function (RDF) and unbalanced force), and meso properties (force chains and their orientations) are characterized and analyzed. The effect of force chains on the densification mechanism is studied. The densification in HVC is reciprocating in accordance with the evolution of local porosity and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Granular flow lubrication is an effective and green modification method to improve the tribological properties of the contact interfaces which has gained widely attention in tool cutting, metallurgy and abrasive polishing fields (Wang, et al , 2021; Zhang et al , 2020; Venu and Venkateswara, 2021). Granular flow generally referred to the aggregation of a large number of solid particles which the size is larger than one micron (Gennes, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granular flow lubrication is an effective and green modification method to improve the tribological properties of the contact interfaces which has gained widely attention in tool cutting, metallurgy and abrasive polishing fields (Wang, et al , 2021; Zhang et al , 2020; Venu and Venkateswara, 2021). Granular flow generally referred to the aggregation of a large number of solid particles which the size is larger than one micron (Gennes, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the properties of the force chain are closely related to the flow state of the particle system which decided directly the lubrication performance of particle system. Zhang et al (2020) pointed out that the strong force chains is produced due to the particle contacting with high friction forces. Wei et al (2019) analyzed the effect of rolling resistance between particles on the force chain network structure.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the discrete element method has been able to carry out not only the microscopic research, but also the macroscopic analysis on granule matter. [13] Furthermore, the concept of the force chain was proposed, and multi-scale mechanical coupling analysis was subsequently made. [14][15][16][17] The force chain is a quasi-linear transfer route of force in a particle system that carries larger forces than other particles, along its normal direction.…”
Section: Introductionmentioning
confidence: 99%
“…[18] The nonlinear sensitive response of granular material can be obtained by using the force chain which is on a mesoscopic scale in multi-scale mechanics. [13] Therefore, it is necessary to study the evolution of force chain in powder compaction process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation